2012
DOI: 10.3390/molecules17044452
|View full text |Cite
|
Sign up to set email alerts
|

Selective Formation of Twisted Intramolecular Charge Transfer and Excimer Emissions on 2,7-bis(4-Diethylaminophenyl)-fluorenone by Choice of Solvent

Abstract: We designed and synthesized a donor-acceptor-donor dye consisting of a 2,7-disubstituted fluorenone with diethylaminophenyl moieties present as strong electron donating groups. Switching between twisted intramolecular charge transfer (TICT) emission and excimer emission was achieved, with no ground state changes, by simply changing the solvent used. In a nonpolar solvent, excimer emission was observed; with increasing polarity, the emission gradually disappeared, and the TICT emission appeared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…At high concentration (5 × 10 −4 –10 −3 M), only the broad emission band at longer wavelength remains but its intensity gradually decreases. The solvatochromic and concentration effects may indicate that the broad peak at around 470 nm is due to a twisted intramolecular charge transfer (TICT) state, as previously observed for tetrapyridinium-based TPE (Grabowski et al, 2003; Shigeta et al, 2012). To investigate the potential AIE behavior of TPE-Im , emission spectra were then recorded in water/THF mixtures with different THF fractions in view of fine-tuning the THF content as well as the aggregation extent (Figure 1D).…”
Section: Resultssupporting
confidence: 52%
“…At high concentration (5 × 10 −4 –10 −3 M), only the broad emission band at longer wavelength remains but its intensity gradually decreases. The solvatochromic and concentration effects may indicate that the broad peak at around 470 nm is due to a twisted intramolecular charge transfer (TICT) state, as previously observed for tetrapyridinium-based TPE (Grabowski et al, 2003; Shigeta et al, 2012). To investigate the potential AIE behavior of TPE-Im , emission spectra were then recorded in water/THF mixtures with different THF fractions in view of fine-tuning the THF content as well as the aggregation extent (Figure 1D).…”
Section: Resultssupporting
confidence: 52%
“…The electronic spectral results for 2-6 can be compared to results from systems where an amino lone pair is not directly attached to fluorenone, but is resonance connected through conjugated hydrocarbon units. Konishi and coworkers 14 reported that 11 has two pp* absorption bands analogous to those in 5-7, and an ICT band exhibiting a solvatochromic shift from 496 nm in hexane to 529 nm in acetonitrile (155 meV); the analogous solvatochromism for 6-7 in hexane versus acetonitrile is 122 meV. However, the luminescence behaviour of 11 is much more complex than that in 2-7, with localized emission at 409-417 nm, TICT emission at 436-450 nm, and excimer bands that shift from 619 nm in toluene to 644 nm in tetrahydrofuran.…”
Section: Comparative Amino Substituent Effects On Fluorenone Acceptorsmentioning
confidence: 99%
“…Since the twisted MB-Py could be considered as a molecule with donor and acceptor constituents (see DFT computations), the positive solvatochromism effect is attributed to the typical twisted intramolecular charge transfer (TICT) which occurs in donoracceptor PAHs. 35 Although the PL emission of MB-Py was slightly shied due to TICT, the maximum of the wavelength was still observed around 430 nm with blue-light emission and no excimer emissions were observed.…”
mentioning
confidence: 99%